Using metabolomics to develop precision medicine strategies to treat nonalcoholic steatohepatitis. Issue 5 (3rd September 2019) - Iruarrizaga-Lejarreta, Marta; Arretxe, Enara; Alonso, Cristina
ABSTRACT: Introduction : Nonalcoholic fatty liver disease (NAFLD) is a health problem of global concern. Nonalcoholic steatohepatitis (NASH), the advanced form of NAFLD, is considered a complex disease and despite the efforts of the medical and researcher community, the current knowledge about it is still limited. As occurs in other medical disciplines, NASH research can benefit from precision medicine approaches. Because the metabolome is highly sensitive to genetic and environmental changes, metabolomics is presently being considered a powerful tool for precision medicine. Areas covered : This review focusses on metabolomics applications in the field of NAFLD/NASH research. We overview metabolomics studies used for a better understanding of factors that act as modifiers of NAFLD susceptibility and progression, such as lifestyle and genetic factors, dysbiosis, and concomitant diseases. We also review applications in the search of noninvasive biomarkers for diagnosis, intervention response, patient stratification and monitoring. Expert opinion : Metabolomics, and especially its branch lipidomics, are ideally placed to study diseases related to deranged lipid metabolism. The search of noninvasive panels able to diagnose NASH and stage fibrosis has become the main application of metabolomics in the NASH/NAFLD field. However, the prediction of patient's response to treatments is one of the most promising strategies.